Determinants of Child Size at Birth and Associated Maternal Factor in Gurage Zone - GM Alemayehu; AG Chernet; KT Dumga (JRI, 2020)
Background: Birth weight plays an important role in infant mortality and mor-bidity, child development, and future health of the child. Reports showed that low birth weight is one of the critical issues in Gugare zone that causes many babies short-term and long-term health consequences and tends to have higher mortality and morbidity. This study examined and identified the determinants of weight of children at birth in Gurage zone. Methods: The survey or the information has been collected on a total of 735,109 reproductive mothers in Gurage zone. Children with age less than 59 months were considered in this study. Ordinal logistic regression techniques used for data analysis using maternal and socio- demographic variables as explanatory variables and size of a baby at birth as the response variable and statistical package for social science (SPSS) version 23 and STATA were used for data analysis purpose.  Results: According to our study, from the sampled children, 30.1%, 44.4% and 25.5% were small in size, medium in size and large in size, respectively. Mater-nal related variables were statistically significant like uneducated mother (β=0.26, p= 0.013), mothers who get antenatal visit care 2-3 times (β=-0.210, p=0.10), source of drinking water (β=0.844, p<0.001) and malaria affected mothers (β=0.344, p< 0.001). Conclusion: Children from rural mothers, uneducated families, mothers who did not get more antenatal care visits, poor families, mothers who drink non-improved water, mothers who are affected by malaria during pregnancy, teenager mothers are small in size at birth.